Whole-cell pertussis vaccine potency assays: the Kendrick test and alternative assays. (October 2014) - Xing, Dorothy; Markey, Kevin; Gaines Das, Rose; Feavers, Ian
<x xml:space="preserve">Abstract</x> Whole-cell pertussis vaccines are still widely used across the globe and have been shown to produce longer lasting immunity against pertussis infection than acellular pertussis vaccines. Therefore, whole-cell vaccines are likely to continue to be used for the foreseeable future. The intracerebral mouse protection test (Kendrick test) is effective for determining the potency of whole-cell pertussis vaccines and is the only test that has shown a correlation with protection in children. Here we review the Kendrick test in terms of international requirements for vaccine potency and critical technical points to be considered for a successful test including test validity, in-house references and statistical analysis. There are objections to the Kendrick test on animal welfare and technical grounds. Respiratory challenge assays, nitric oxide induction assay and serological assays have been developed and have been proposed as possible methods which might provide alternatives to the Kendrick test. These methods and their limitations are also briefly discussed. Establishment of validated in vitro correlates of protection has yet to be achieved. New technical developments, such as genome sequence and the use of gene microarrays to screen responses triggered by vaccine components may also provide leads to alternative assays to the Kendrick test by identifying biomarkers of protection.